INTERNATIONAL ORGANIZATIONS AND THE SAFETY OF CONFLICT JOURNALISTS: analysis of the characteristics, structure, and resources of their virtual press rooms - Una Endemaño, Annette; Taboada Castell, Claudia; Iturregui Mardaras, Leire; Cantalapiedra González, María José (Brazilian journalism research, 2024)
ABSTRACT – The safety of journalists who cover conflicts has been an issue that has raised concern within the War in Ukraine (2022) and the one in Gaza (2024), which has led to international organizations to raise awareness among international organizations to develop new measures and strategies to guarantee the protection of journalists. In a context in which organizations become creators of content and build connections with their audiences, this paper analyses the main characteristics, structure, content, and communication channels of the Virtual Press Rooms of international organizations dedicated to the safety of journalists. The use of the Press Rooms as storage for information and the lack of unified criteria in their naming, the lack of a target audience corporate image strategies, opens up new research lines regarding the role of these organizations in supplying documentation to aid journalists. RESUMO – A segurança dos jornalistas que enfrentam conflitos foi um tema que saltou na agenda pública com a Guerra da Ucrânia (2022) e o conflito em Gaza (2023), e levou organizações internacionais a realizar petições públicas para implementar novas medidas e estratégias vinculadas à proteção dos periodistas. Em um contexto em que as organizações se convertem em criadoras de conteúdo e vínculos com seus públicos, este trabalho analisa as características, estrutura, conteúdo e recursos de interação das salas de imprensa virtuais (SPV) das organizações internacionais dedicadas à segurança dos periodistas sobre o terreno. O uso das salas de imprensa como repositório de conteúdo informativo, a desavença de critérios em sua denominação, a falta de um objetivo público definido e a presença de recursos e manuais intermitentes para os jornalistas no terreno, abrem novos horizontes de estudo sobre o papel destas organizações como administradoras de materiais especializadas em segurança durante coberturas de conflito. RESUMEN – La seguridad de los periodistas que cubren conflictos ha sido un tema que ha saltado a la agenda pública con la Guerra de Ucrania (2022) y el conflicto en Gaza (2023), y ha llevado a organizaciones internacionales a realizar peticiones públicas para implementar nuevas medidas y estrategias vinculadas a la protección de los periodistas. En un contexto en el que las organizaciones se convierten en creadoras de contenidos y vínculos con sus públicos, este trabajo analiza las características, estructura, contenidos y recursos de interacción de las salas de prensa virtuales (SPV) de las organizaciones internacionales dedicadas a la seguridad de los periodistas sobre el terreno. El uso de las salas de prensa como almacén de contenidos informativos, la desavenencia de criterios en su denominación, la falta de un público objetivo definido y la presencia intermitente de recursos y manuales para los periodistas en el terreno, abren nuevos horizontes de estudio sobre el papel de estas organizaciones como suministradoras de materiales especializados en seguridad durante coberturas de conflicto.